Influence of inoculum-to-substrate ratio on biogas enhancement during biochar-assisted co-digestion of food waste and sludge - Johnravindar, Davidraj (Environmental technology, 2023)
High accumulation of volatile fatty acids (VFAs) is one of the major concerns during mesophilic anaerobic co-digestion of food waste (FW) and sewage sludge (SS). Therefore, improving the stability of the anaerobic digestion process could surpass quick acidification while accelerating methanogenesis. In this study, the suitability of biochar-assisted co-digestion was evaluated at different inoculum and substrate ratios (I/S ratios: 0.1, 0.3, 0.6, and 0.9). The maximum methane yield of 256.85 mL/gVSadd was observed at an I/S ratio of 0.6. The results indicated fast volatile solid removal (∼ 47.17% to 73%) and a critical role of biochar addition in alleviating the underlying inhibitions. Substantial changes in the microbial community composition including Methanosata, Methanobrevibacter, and Methanosarcina were also observed which predominated and stabilised the methanogenesis process at higher I/S ratios. These results emphasised that the anaerobic co-digestion of FW/sludge is a promising approach, wherein the biochar amendment at different I/S ratios should be well maintained to avoid inhibitions from excess microbial VFA acidification of organic waste feedstocks